Togo : Staff-Monitored Program. (IMF Staff Country Reports; Country Report ;, 2007)
This paper focuses on the Staff-Monitored Program (SMP) for Togo. The SMP aims to support the preparation of a realistic 2007 budget, with a moderate primary adjustment; anchor budget execution in a pre-election period; strengthening fiscal governance, especially on expenditure management; initiating urgent banking sector reforms; and preparing for state-owned enterprise reforms. During the SMP, the authorities intend to update Togo's Interim Poverty Reduction and Growth Strategy Paper (I-PRSP), set up a program monitoring mechanism, and reengage with donors, whose technical and financial assistance will be crucial for medium-term prospects.